Peran Mediasi Kepuasan Kerja Pada Pengaruh Dukungan Organisasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara - Hendra Sutrisno Marbun; Jufrizen Jufrizen (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to examine and analyze the effect of organizational support and work environment on employee performance mediated by job satisfaction at the Office of Dinas Ketahanan Pangan dan Peternakan Provinsi Sumatera Utara directly or indirectly. The approach used in this study is a causal approach. The population in this study were all state civil servants at the Office of Dinas Ketahanan Pangan dan Peternakan Provinsi Sumatera Utara. The sample in this study used a sample of the slovin formula totaling 68 state civil servants at the Office of Dinas Ketahanan Pangan dan Peternakan Provinsi Sumatera Utara. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that direct organizational support, work environment and job satisfaction have a significant effect on employee performance and indirectly organizational support and work environment have a significant effect on employee performance mediated by job satisfaction at the Office of Dinas Ketahanan Pangan dan Peternakan Provinsi Sumatera Utara.